First records of myxomycetes from Laos - Thida W Ko Ko (2018)
Records of myxomycetes obtained as a result of a field surveys carried out at two localities in Laos during October 2008 and a single locality during November 2010 were supplemented with records of species appearing in moist chamber culture on samples of various types of dead plant material collected during the field surveys. These efforts yielded a total of at least 44 species in 17 genera. There appear to be no previous records of myxomycetes from Laos. As such, the study reported herein represents a starting point for future studies to document this group of organisms for another region of Southeast Asia. © 2012 J. Cramer in Gebr. Borntraeger Verlagsbuchhandlung, Stuttgart, Germany.